Sistem Pakar Delirium Pasien COVID-19 Pada Lansia Menggunakan Metode Certainty Factor dan Forward Chaining - Ernawati, Ernawati; Hidayatullah, Deny; Fitri, Iskandar (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
In this study, it is related to an expert system for detecting delirium in COVID-19 patients which has never been done in Indonesia in previous studies, related to the method used by researchers to compare 2 hybrid methods, namely the Certanty Factor method with the Forward Chaining method compared to the Bayes method and Forward Chaining . From the results of the comparison, a higher confidence value is obtained, namely the certainty factor and forward chaining as a method in making an expert system application for detecting delirium in elderly COVOD-19 patients. From the results of the application test, which is compared with the calculation results, it is known that from the 20 patient samples, 70% of the samples stated Possibility and 30% stated  Most Likely from the diagnosed disease. The certainty factor technique is applied to calculate the certainty value of a fact or rule and the forward chain method is used to draw conclusions that will help diagnose a disease.